Statement on the Positive Effects of Mulching with Straw and Black Nylon on the Growth and Yield of Green Onions - Mohammed Salim Ahmed Ai-Allaf; Warka Saad Mohammed (American Journal of Biology and Natural Sciences, 2025)
The study was conducted in one of the private sector fields in the Sheikh Mohammed area in Mosul. Planting took place on 11/5/2022 for the fall semester. The experiment included evaluating three types of covers: straw cover, half cover with black nylon, and full cover with black nylon. In addition to planting in open soil for the purpose of producing green onions without irrigation. The CRD design was used in this experiment, where the first treatment was without soil covering, the second treatment was straw covering, the third treatment was covering half the soil with black nylon, and the fourth treatment was Mulching completely with black nylon, with three replicates for each factor. Two lines of onions were planted, the distance between each line and the next was 25 cm, and the distance between each plant was 10 cm. The (Bashiqi) variety was planted. The results showed that when planting and producing green onions using full soil coverage without irrigation, it gave the best significant results compared to planting in open soil for all the studied characteristics, as the weight of the plant in the case of full soil coverage was (206.19) g, while the weight of the plant in the case of open soil was (57.78) g.